EFEECTIVENES OF PQ4R METACOGNITIVE STRATEGY BASED READING LEARNING MODELS IN JUNIOR HIGH SCHOOL - Sarimanah, Eri (PPs UNJ, 2016)
The objective of research is to find out the efectivenes of metacognitive Preview, Question, Read, Reflect, Recite, Review (PQ4R) strategy based reading learning model to improve SMP studentsâ reading ability. The method applied in this study is research and development by using both qualitative and quantitative approaches. The research result shows that the ideal learning model needed by the students is metacognitive PQ4R strategy based reading learning model. Structurally, this learning model is viable, relevant, and suitable with the principles of learning model development, both from substantial view and the structural model. Based on the trial result with experimental research design (experimental and control groups), metacognitive PQ4R strategy based reading learning model is effective to be used to improve SMP studentsâ reading ability. Even the learning outcome is better than the reading class done by the teacher who does not use metacognitive PQ4R strategy. learning metacognitive reading strategies based PQ4R junior high school students are more effective than learning to read that teachers without the use of metacognitive strategies PQ4R with the calculation results of test of 5.975 t test is greater than t table 1.67. So it can be concluded that the learning model based reading metacognitive strategies PQ4R effective and fit for use in secondary schools.